Transformation of Gig Economy Labor Structures: Implications for Social Security Accounting and New Economic Vulnerability Risks - Delila Rambe (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2026)
The global labor market is experiencing a profound metamorphosis due to the rapid expansion of digital platforms, which challenges traditional employment paradigms and social protection frameworks. This study investigates the transformation of gig economy labor structures and its specific implications for social security accounting and emerging economic vulnerability risks. Utilizing a quantitative design with an ex post facto approach, the research analyzes a weighted sample of 2,185,340 individuals from the Indonesian National Labor Force Survey (Sakernas) and BPJS Ketenagakerjaan datasets across major metropolitan areas, including Jakarta and Surabaya. Variables examined include algorithmic management intensity, contribution persistence, and the precarity index. Results indicate that while platforms offer "pseudo-flexibility," workers are subjected to rigid algorithmic subordination, leading to significant income volatility. A critical finding is the 75.70% gap in old-age security participation among gig workers compared to formal employees, coupled with a low contribution persistence ratio of .34. These results reveal that conventional social security accounting, predicated on fixed monthly cycles, is incompatible with the fragmented nature of platform-based cash flows. The implications suggest a looming welfare crisis for future elderly populations and systemic fiscal instability for national insurance funds. The study concludes that an urgent transition toward API-integrated, real-time micro-contribution systems is necessary to bridge the protection gap. Future research should explore blockchain-based social security portability to ensure adaptive resilience in the digital era.